READABILITY OF THE DISABLEMENT OF THE PHYSICALLY ACTIVE (DPA) SCALE IN PEDIATRIC ATHLETES. Issue 3 (31st March 2019) - Marshall, Ashley N.; Lam, Kenneth C.
Background: The assessment of patient outcomes in pediatric (ie, youth and adolescent) athletes is critical for comprehensive and whole person healthcare. The Disablement of the Physically Active scale (DPA) is a relatively new generic patient-reported outcome measure (PROM) that was designed specifically for athletic and highly functional patient populations. While the DPA has been used to evaluate health-related quality of life (HRQOL) in adults, little is known about its use in pediatric athletes. The selection of PROMs for pediatric athletes presents with unique challenges, particularly regarding the ability of these athletes to effectively understand the instruments to which they are completing. Therefore, the purpose of this study was to examine the readability of the DPA in pediatric athletes through (1) participant-based and (2) computer-based analyses. Methods: Participant-based analysis was utilized to conduct a preliminary investigation into the subjective readability (ie, a participant's perceived ability to successfully read the material) of the DPA. Participants were youth athletes (n=13, age=8.7±1.3 years) recruited from a local community athletics league. An investigator administered the San Diego Quick Assessment of Reading Ability to determine each participant's current reading grade level. Participants were then instructed to read each item of the DPA and circle any words that they did not understand. Frequency counts and percentages were determined for each word identified by participants, within each item of the DPA. Computer-based analysis was utilized to assess the objective readability of the DPA. The Flesch Reading Ease (FRE), Flesch-Kincaid Reading Level (FK), and Gunning Fog Index (FOG) scores were calculated for each item of the DPA. FRE scores range from 0 to 100, with lower scores indicating more difficult reading material. The FRE score is converted to an approximate reading level (FK), ranging from pre-primer (<0) to college (>12), with higher reading level indicating more difficult reading material. Similar to the FK formula, the FOG formula computes to an approximate reading grade level associated with the U.S. education system. Summary statistics (mean± standard deviation, median, and range) were used to report scores for each DPA item. We also reported the number (%) of items that exceeded the 5th – 6th grade reading level, which is the maximum recommended threshold for pediatric patients. Results: It was determined that the average reading grade level of the participants was 3±1.4 years. In regards to subjective readability, participants did not understand an average of 22.1% (48.3/219 words) of the entire DPA scale, with a range across items of 3.1% (Pain = 0.15/5 words) to 34.9% (Overall Fitness = 5.2/15 words). There were 40 instances where greater than 50% of the participants did not recognize a word, and seven words throughout the scale that 100% (13/13) of the participants did not understand: endurance, stability, pivoting, coordination, cardiovascular, endurance and colleagues. For objective readability, FRE scores ranged from 5.8 (very confusing) to 119.7 (very easy) across items. The mean and median across all items was 42.4±33.4 (difficult), and 41.4 (difficult), respectively. The FK reading level ranged from -2.8 (pre-primer) to 13.8 (college), with a mean score of 8.8±4.8 and median score of 8.9. The FOG reading level ranged from 1 (1st grade) to 13.8 (college), with a mean score of 9.3±3.8 and median score of 10.5. When considering both the FK and FOG scores, 81.8% (9/11) of the items exceeded the 5th – 6th grade reading level threshold. Conclusions/Significance: These findings indicate that the overall readability of the DPA may not be appropriate for pediatric athletes. Thus, findings using the DPA in pediatric athletes for clinical or research purposes should be interpreted with caution. Future research is warranted to develop a pediatric version of the DPA, utilizing the results of this study for guidance, as no other generic PROM currently exist for assessing HRQOL specifically in youth and adolescent athletes.